2018
DOI: 10.1111/nmo.13397
|View full text |Cite
|
Sign up to set email alerts
|

Increased levels of substance P in patients taking beta‐blockers are linked with a protective effect on oropharyngeal dysphagia

Abstract: We have found that serum and saliva SP levels are greater in patients TBB. This increase in SP levels could be the action mechanism by which beta-blockers protect patients from OD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 54 publications
(62 reference statements)
0
16
0
Order By: Relevance
“…Ye et al [41] China Comparison of two bedside evaluation methods of dysphagia in patients with acute stroke. Miarons et al [42] Spain Increased levels of substance P in patients taking beta-blockers are linked with a protective effect on oropharyngeal dysphagia. 0 (low risk) 4 Westmark et al [43] Denmark The cost of dysphagia in geriatric patients.…”
Section: Quality Of Studies In the Srmentioning
confidence: 99%
“…Ye et al [41] China Comparison of two bedside evaluation methods of dysphagia in patients with acute stroke. Miarons et al [42] Spain Increased levels of substance P in patients taking beta-blockers are linked with a protective effect on oropharyngeal dysphagia. 0 (low risk) 4 Westmark et al [43] Denmark The cost of dysphagia in geriatric patients.…”
Section: Quality Of Studies In the Srmentioning
confidence: 99%
“…ACEi and Dipeptidyl-Peptidase IV Inhibitors (DPP-4i) have been reported to improve the swallowing reflex (Cunningham and O'Connor, 1997;Nakayama et al, 1998). Beta-blockers were found to be associated with lower dysphagia prevalence in the elderly patients (Miarons et al, 2018). Nevertheless, none of the studies clarified the mechanisms underlying the potential positive effects of these drugs on dysphagia, although a weak role of substance P (SP), a neuropeptide that enhances swallowing and cough reflexes, was hypothesized (Jin et al, 1994;Imoto et al, 2011;Canning et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…These agents either stimulate swallowing-related neural pathways in the peripheral or central nervous systems or directly modifying muscular function. 13 To date, the drug classes that have been studied in the area of swallowing and oropharyngeal dysphagia include transient receptor potential vanilloid 1 (TRPV1) agonists, [14][15][16][17][18][19][20] transient receptor potential ankyrin 1 (TRPA1) agonists, 21 transient receptor potential melastatin 8 (TRPM8) agonists, 22 levodopa, [23][24][25] other dopaminergic agents, 26 calcium blocking agents, 27,28 dopamine D2 receptor antagonists, 29 angiotensin-converting enzyme (ACE) inhibitors, 30 beta blockers, 31 nitric oxide donors 32 and acetylcholinesterase inhibitors. 33 Studies have suggested that these drugs may improve the swallowing reflex or reduce incidence of aspiration pneumonia in dysphagic patients.…”
Section: Introductionmentioning
confidence: 99%
“…One mechanism is stimulation of afferent neural pathways for swallowing, for example receptors (TRPV1, TRPA1 and TRPM8) located in the oropharynx, 34 through TRP channel agonists 14‐22 . Another mechanism involves increasing the level of or decreasing degradation of substance P, which is a neuropeptide known to enhance the swallow reflex, 35 through capsaicin, ACE inhibitors or beta blockers 17,30,31,36 . Levodopa and dopaminergic agents may improve swallowing through improving dopamine metabolism 23‐26 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation